ENTREPRENEURSHIP: SINGLE MOTHER'S FAMILY SOLUTIONS IN BUILDING FAMILY COMMUNICATION - Indrayanti -; Sennahati -; Mattarima -; Saharuddin - (Journal of Entrepreneur, Business and Management, 2023)
Single mothers have a dual role where they must be able to take care of children while working to support their family. Being an entrepreneurship is a single mother's choice so that the role of a father who provides for as well as the role of a mother who takes care of children can be fulfilled. Without having to leave home, he can earn money besides that he can manage his own time so that he can take care of children without feeling any pressure. This research methodology uses qualitative descriptive methods through a case study approach. Sampling is done intentionally (non-random). The respondents in this study were a single mother of online shopping owners, the longest serving employee and loyal customer and the study was conducted with in-depth interviews. Through the principle of siri na pesse in running their business, single mothers use a family system for all their employees and loyal customers. The form of family relations is in the form of family allowances if one of the families is sick or holidays, or sometimes also a form of giving clothes if sales are above average. While loyal customers often occur even if they just hang out together at a café or visit if someone is sick. There is still a stigma attached in society that work is when he is an employee makes them easily frustrated if they are not accepted in a company and end up as unemployed. By becoming an entrepreneur, especially a single mother, it provides an opportunity to have a job while taking care of children without having to leave the house.